1981
DOI: 10.1111/j.1476-5381.1981.tb09147.x
|View full text |Cite
|
Sign up to set email alerts
|

THE ACTION OF DANTROLENE SODIUM ON RAT FAST AND SLOW MUSCLE in vivo

Abstract: 1Rats, anaesthetized with urethane, were injected intravenously with dantrolene sodium in a carrier solution of 5% mannitol taken to pH 10 with NaOH. This carrier solution itself was without effect on extrafusal muscle contraction. 2 Dantrolene sodium (5 mg/kg) had a greater depressant action on the twitch contraction of the fast extensor digitorum longus (EDL) muscle than on the slow soleus (SOL) muscle. The EDL twitch was depressed to 25.9% + 1.2% (mean + s.e. mean, n = 7) of control whereas the SOL twitch w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
32
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 15 publications
10
32
2
Order By: Relevance
“…In each preparation care was taken to stabilize the proximal tendon of the muscle whilst the distal tendon, now cut from its insertion, was attached to the force transducer (Devices 2ST 05, 0-100 g). Thereafter the bath was filled with pre-warmed liquid paraffin maintained at 35 to 37°C by warm water circulating through a second chamber in the base of the bath (see Andrew & Part, 1972; Leslie & Part, 1981a (Andrew & Part, 1972).…”
Section: Methodsmentioning
confidence: 99%
“…In each preparation care was taken to stabilize the proximal tendon of the muscle whilst the distal tendon, now cut from its insertion, was attached to the force transducer (Devices 2ST 05, 0-100 g). Thereafter the bath was filled with pre-warmed liquid paraffin maintained at 35 to 37°C by warm water circulating through a second chamber in the base of the bath (see Andrew & Part, 1972; Leslie & Part, 1981a (Andrew & Part, 1972).…”
Section: Methodsmentioning
confidence: 99%
“…That was accomplished by using dantrolene sodium, a specific inhibitor of sarcoplasmic reticulum Ca 2+ release (14)(15)(16). The purpose of this study was to investigate if staircase potentiation could be restored in atrophied muscle after dantrolene treatment without concomitant increases in R-LC phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies on muscle fibers suggested the RyR as the potential target for the action of dantrolene (25,26), and respective binding sites were mapped to the protein (27)(28)(29). However, no action of dantrolene was found in most studies on single RyRs incorporated into lipid bilayers (26,30,31).…”
mentioning
confidence: 99%